Contraceptive Counseling in the Zika Era: Primary Care Providers' Perspective [07J]. (May 2020) - Kaiser, Jennifer; Sanders, Jessica; Simmons, Rebecca; Gawron, Lori M.; Turok, David Keith
Abstract : INTRODUCTION: The 2015 Zika virus (ZIKV) outbreak emphasized the imperative for contraceptive counseling for at-risk populations such as Latinx women. This study assessed primary care providers' knowledge, perception of risk, and approach to contraceptive counseling in response to ZIKV. METHODS: We performed a sequential mixed-methods, cross-sectional study with a survey and semi-structured interview. From 06/2018 to 08/2018 we recruited primary care providers from a federally qualified health organization in the Salt Lake City area that provides preventive care to non-pregnant Latinx women of reproductive age. The survey assessed demographics, contraceptive and ZIKV knowledge, and CDC ZIKV guideline adherence. The Health Belief Model informed our interview guide on contraceptive and ZIKV counseling. We performed descriptive analyses on survey data and analyzed qualitative data for dominant themes. RESULTS: Twenty-two of 40 (57%) providers participated. Twelve (55%) are family medicine physicians, seven are physician assistants (32%), and three are nurse practitioners (14%); 53% are women, and 96% identify as white. On contraceptive and ZIKV knowledge questions, providers averaged 69% and 81% correct respectively. Sixty-five percent reported CDC ZIKV guideline adherence. Qualitative themes include conditional ZIKV risk, neonatal-related severity of ZIKV, specific cues to action for counseling about ZIKV and contraception, and omission of the ZIKV risk to non-pregnant women who may become pregnant. CONCLUSION: Primary care providers perceive the risk of ZIKV; however, their knowledge, guideline adherence, and perception of risk do not translate into ZIKV-aware counseling. Our results demonstrate the need for action plans that ensure practice changes in response to emerging infectious diseases.